Dinamika Tutupan Lahan Di Taman Nasional Kerinci Seblat : Land Cover Dynamics in Kerinci Seblat National Park - Tegar wirayuda; Rudi Hilmanto; Arief Darmawan; Dian Iswandaru (Jurnal Silva Tropika, 2026)
ABSTRACT The largest conservation area on the island of Sumatra is Kerinci Seblat National Park (TNKS), which stretches across four provinces: West Sumatra, South Sumatra, Bengkulu, and Jambi. This area experiences various pressures that trigger land cover changes caused by natural and human factors. This study aims to determine land cover changes that occurred between 2013, 2018, and 2023 and to determine the anthropogenic activities that influence these changes. Land cover analysis was conducted using the supervised classification method with the random forest algorithm on the Google Earth Engine platform. Image classification resulted in five classes: water bodies, forests, horticultural land, open land, and shrubs. To identify the factors influencing land cover changes, an ethnoecological approach was used. The classification results were tested using the overall accuracy method, with accuracy values ​​of 88.44% in 2013, 89.94% in 2018, and 85.17% in 2023. The results showed that in the 2013–2018 period there was a decrease in forest cover, water bodies, and shrubs, while horticultural land and open land experienced an increase. In the 2018–2023 period, forest cover and open land decreased, while water bodies, horticulture, and shrubs increased. The dynamics of land cover are influenced by various anthropogenic activities such as forest encroachment, land conversion, illegal mining, historical land ownership, and economic pressures on the community after the Covid-19 pandemic. In addition, natural factors such as floods also influence changes in land cover in the TNKS area. Therefore, increased monitoring and security of the area and strengthening of conservation-based community empowerment are needed.   Keywords: ethnoecology, google earth engine, kerinci seblat national park, land cover dynamics, random forest   ABSTRAK Kawasan konservasi terluas di Pulau Sumatera adalah Taman Nasional Kerinci Seblat (TNKS) yang terbentang di empat provinsi yaitu Sumatera Barat, Sumatera Selatan, Bengkulu dan Jambi. Kawasan ini mengalami berbagai tekanan yang memicu perubahan tutupan lahan yang disebabkan oleh faktor alam dan manusia. Penelitian ini bertujuan untuk mengetahui perubahan penutupan lahan yang terjadi pada kurun waktu tahun 2013, 2018 dan 2023 serta mengetahui aktivitas antropogenik yang mempengaruhi perubahan tersebut. Analisis tutupan lahan dilakukan menggunakan metode supervised classification dengan algoritma random forest pada platform Google Earth Engine. Klasifikasi citra menghasilkan 5 kelas yaitu badan air, hutan, lahan hortikultura, lahan terbuka dan semak belukar. Untuk mengetahui faktor-faktor yang mempengaruhi perubahan tutupan lahan menggunakan pendekatan etnoekologi. Hasil klasifikasi diuji menggunakan metode overall accuracy, dengan nilai akurasi sebesar 88,44% pada tahun 2013, 89,94% pada tahun 2018, dan 85,17% pada tahun 2023. Hasil penelitian menunjukkan bahwa pada periode 2013–2018 terjadi penurunan tutupan hutan, badan air, dan semak belukar, sementara lahan hortikultura dan lahan terbuka mengalami peningkatan. Pada periode 2018–2023, tutupan hutan dan lahan terbuka menurun, sedangkan badan air, hortikultura, dan semak belukar meningkat. Dinamika tutupan lahan tersebut dipengaruhi oleh berbagai aktivitas antropogenik seperti perambahan hutan, alih fungsi lahan, pertambangan ilegal, historis kepemilikan lahan, serta tekanan ekonomi masyarakat pasca pandemi Covid-19. Selain itu, faktor alam seperti banjir turut memengaruhi perubahan tutupan lahan di kawasan TNKS. Oleh karena itu, diperlukan peningkatan pengawasan dan pengamanan kawasan serta penguatan pemberdayaan masyarakat berbasis konservasi.   Kata kunci: dinamika tutupan lahan, etnoekologi, google earth engine, random forest, taman nasional kerinci seblat